INVESTIGATING AUDIT QUALITY DETERMINANTS : EVIDENCE FROM THE MINING INDUSTRY IN INDONESIA - Putra Pamungkas, Wahyu Ragil; Rofiqoh, Ifah (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2025)
This study analyzes the impact of audit tenure, audit committee, audit fees, audit rotation, auditor specialization, and leverage on audit quality. A quantitative method was employed using secondary data sources in the form of annual reports and audited financial statements. The sample consisted of mining sector companies listed on the Indonesia Stock Exchange from 2019 to 2023, utilizing purposive sampling techniques. 38 companies were analyzed, resulting in 190 observations over the specified period. Panel data regression analysis was employed to test the proposed hypotheses. The research findings show that audit tenure and audit rotation negatively impact audit quality, while the audit committee, audit fees, auditor specialization, and leverage do not have a significant effect on audit quality.